REINVENTING “PATUNTUNG RELIGION” IN SOUTH SULAWESI, INDONESIA - Muhammad Takbir; Rizal Mustansyir; Sindung Tjahyadi (JICSA : Journal of Islamic Civilization in Southeast Asian, 2021)
This study re-scritinizes Patuntung as a religious category. The aim is to see the various reasons why Patuntung is called religion and to re-examine the basic assumptions of these reasons. The method used in this research is critical discourse analysis which refers to the Foucauldian genealogy theory. As a result, it was found that the Patuntung religion was a new invention from Dutch Christian missionaries in the colony which was later affirmed by Indonesian scholars in the context of Islam later. In addition, there is a construction bias towards Patuntung religion, both world religions (especially Christianity and Islam) and euro-centric bias. Thus, the term religion attached to Patuntung itself is ambiguous.